Unsettling whiteness : Kipling's Boers and the case for a white subalternity - Retief, Zed (Department of English Language and Literature, 2016)
The 'Bard of Empire' Rudyard Kipling's Boer War (or South African War) writing has largely been dismissed as jingoism. Yet these texts may well have something to contribute both to existing discourses around colonialism, as well as to our understanding of South Africa's deeply intertwined racial and political history. While his Indian writing is also informed by an imperial ideology, Kipling's South African writing is more overtly dogged by imperial contradictions and a lack of thematic and narrative clarity. As such, his Indian writing provides a useful touch-point throughout this thesis. Of particular interest here is the seeming tension between Kipling's representations of the Boers as both 'degenerate' and as 'white'. Broadly, in the course of this thesis this tension is approached in two ways. This first of these considers the motivating forces behind Kipling's racialization of the Boers, specifically in terms of the anxieties provoked by the colonisation of another 'white' race. As such, this anxiety is read as stemming largely from a perceived cultural trangression on the part of the Boers - an inversion of the dynamic that typifies many of Kipling's Indian texts. Following this, some of the rhetorical devices by which Kipling (re)enforces notions of 'white loyalty' and, more broadly, a strict visually marked racial hierarchy, are considered. In so doing, some of Kipling's Boers are read as, somewhat surprisingly, representing a silenced subaltern voice who are made to speak exclusively in support of the empire. Through the commingling of these representations Kipling seems to participate in a discursive conflict over the conception of whiteness both within the empire and South Africa.